Field guide to the future: four ways for communities to think ahead - Evans, K.; Velarde, S.J.; Prieto, R.; Rao, S.N.; Sertzen, S.; Davila, K.; Cronkleton, P.; Jong, W. de (Center for International Forestry Research (CIFOR), ASB, World Agroforestry Center, 2006)
This book is a practical, step-by-step manual for using scenario-based methods in communities. The guide has been written in straightforward language and organized as a teaching tool to facilitate the use of the methods without additional training. It explains methods to help communities think ahead and plan for change. These methods are: Scenarios, Projections, Visioning and Pathways. The field guide begins with a brief discussion about communities that depend on natural resources, thinking about the future and why it is important for communities to think ahead. Next, it briefly introduce four methods for thinking about the future, describing hypothetical situations where each might be applied. The authors provide a comparative matrix to make it easier to decide between methods in a given context. Then discuss concepts such as participation, mental maps, uncertainty and complexity. In the second section "Getting Ready" the book explains how to plan for an exercise in thinking ahead in a community, with suggestions for organizing an event, selecting participants and monitoring progress. The third section "Facilitating the Methods Step by Step" dwelves into the details.